BMN-like sectors in 4d N $$ \mathcal{N} $$ = 4 SYM with boundaries and interfaces - Andrea Chaney; Christoph F. Uhlemann (Journal of High Energy Physics)
Abstract 4d N $$ \mathcal{N} $$ = 4 SYM admits half-BPS boundaries, defects and interfaces as well as compactifications to 3d N $$ \mathcal{N} $$ = 4 SCFTs, realized as intersections of D3, D5 and NS5 branes. We explore operators with large R-charge. We identify Penrose limits in the holographic duals with geometry AdS4 × S2 × S2 × Σ, which describe, for each theory, a spectrum of ‘seed’ operators which each give rise to a BMN-like sector described by a pp-wave. We relate the number of BMN-like sectors to the flavor symmetry of the CFT. For a sample of theories including the Janus interface, D3/D5 BCFTs and BCFTs with 3d SCFTs on the boundary, we determine the spectra of nearby operators and discuss the field theory realization of the seed operators. We further identify families of Penrose limits which give rise to more general pp-wave sectors.